2014
DOI: 10.3126/kumj.v10i4.10992
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Cholera in Tilathi VDC Saptari Nepal

Abstract: BackgroundOn 2011, Cluster of cholera cases was reported in the Tilathi VDC of Saptari, Nepal. ObjectiveThe outbreak was investigated to identify the etiological agent and possible source of infection and guiding the prevention and control measures. MethodsDemographic and clinical details were collected from the suspected case-patients, and the outbreak was described by time, place, and person. Focus group discussion and Key informant interview were conducted to assess the practice of sanitation, source of dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 8 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Contrary to this, adult populations of age group 20–30 years were highly infected accounting for 8.7% as compared to all other aged groups (3.4%) in our context (p = 0.018). The studies by Kansakar et al [ 22 ] and Yadav et al [ 32 ] found similar results in which most of the infected patients were adults aged 20 to 29 years and 15 to 29 years respectively. The greater incidence of infections in these groups was found because of their food habits outside the home including consumption of street food.…”
Section: Discussionmentioning
confidence: 57%
“…Contrary to this, adult populations of age group 20–30 years were highly infected accounting for 8.7% as compared to all other aged groups (3.4%) in our context (p = 0.018). The studies by Kansakar et al [ 22 ] and Yadav et al [ 32 ] found similar results in which most of the infected patients were adults aged 20 to 29 years and 15 to 29 years respectively. The greater incidence of infections in these groups was found because of their food habits outside the home including consumption of street food.…”
Section: Discussionmentioning
confidence: 57%
“…However, despite the presence of EWARS in nearly 80% of the outbreaks examined, the median delay to response was 10 days. Where EWARS was used successfully to link early detection with a preliminary and robust response, for example in Afghanistan (2010-1), Nepal (2011-6), and Northern Nigeria (2018), a timely response was judged to be dependent on adequate and trained human resources (e.g., district-level rapid response teams or local health facility staff capable of multidisciplinary investigation and a generic response [63,162]), and the ability to mount at least a preliminary response moving forward independent of laboratory confirmation [52,75,100,101,139,161,171]. For example, investigation and response were integrated in Afghanistan (2010) where a local NGO was trained rapidly to carry out a comprehensive community response, as they had more access to the area than health authorities in an insecure area [52].…”
Section: Discussionmentioning
confidence: 99%
“…In Somalia, faster response in insecure urban areas using EWARS in 2016 and 2018 can be compared to a lack of a comprehensive early response during ongoing transmission over 2 months in 2008 (14-and 19-day delays versus 2-month delay, ID 54-56). Nepal's EWARS facilitated rapid detection and response to clusters from 2011 onwards (total delays 6-9 days, ID 42-44) [75,130,162]. In 2016, RDT capacity was added at health facilities to enable better discrimination between alerts of cholera or diarrhea due to other pathogens [161].…”
Section: Factors Associated With Delaysmentioning
confidence: 99%
“…Other studies have documented youthful populations as the most affected age group. 10,14,15 In direct contrast to this, other studies have reported children and elderly people mostly affected by cholera. 16,17 About 37.2% (123/331) of the collected stool samples and rectal swabs from various health facilities in the metropolis were confirmed positive for cholera.…”
Section: Discussionmentioning
confidence: 88%